Somatic TP53 variants frequently confound germ-line testing results. (August 2018) - Weitzel, Jeffrey; Chao, Elizabeth; Nehoray, Bita; Van Tongeren, Lily; LaDuca, Holly; Blazer, Kathleen; Slavin, Thomas; FACMG, D; Pesaran, Tina; Rybak, Christina; Solomon, Ilana; Niell-Swiller, Mariana; et al.
Abstract Purpose Blood/saliva DNA is thought to represent the germ line in genetic cancer-risk assessment. Cases with pathogenicTP53 variants detected by multigene panel testing are often discordant with Li-Fraumeni syndrome, raising concern about misinterpretation of acquired aberrant clonal expansions (ACEs) withTP53 variants as germ-line results. Methods Pathogenic TP53 variants with abnormal next-generation sequencing metrics (e.g., decreased ratio (<25%) of mutant to wild-type allele, more than two detected alleles) were selected from a CLIA laboratory testing cohort. Alternate tissues and/or close relatives were tested to distinguish between ACE and germ-line status. Clinical data and Li-Fraumeni syndrome testing criteria were examined. Results Among 114, 630 multigene panel tests and 1, 454TP53 gene-specific analyses, abnormal next-generation sequencing metrics were observed in 20% of 353TP53 -positive results, and ACE was confirmed for 91% of cases with ancillary materials, most of these due to clonal hematopoiesis. Only four met Chompret criteria. Individuals with ACE were older (50 years vs. 33.7;P = 0.02) and were identified more frequently in multigene panel tests (66/285; 23.2%) than inTP53 gene-specific tests (6/68; 8.8%, P = 0.005). Conclusion ACE confounds germ-line diagnosis, may portend hematologic malignancy, and may provoke unwarranted clinical interventions. Ancillary testing to confirm germ-line status should precede Li-Fraumeni syndrome management.